Outcomes of patients admitted to the intensive care unit with sepsis and septic shock in Saudi Arabia over 16 years - Yaseen M. Arabi; Musharaf Sadat; Hasan M. Al-Dorzi; Hani Tamim; Saad AlQahtani; Haytham Tlajyeh; Farhan Zayed Alenezi; Tarek Dabbagh; Rasha Alanazi; Asma Alanazi; Nabiha Tashkandi; Wejdan Alrassasmah; et al. (Journal of Infection and Public Health, 2025)
Background: We examined the outcomes of patients with sepsis and septic shock admitted to the intensive care unit (ICU) in a tertiary care hospital in Saudi Arabia over 16 years. Methods: A retrospective cohort study was carried out using data collected prospectively in an ICU database. We included all patients admitted between January 1, 2002, and December 31, 2017, with sepsis defined by Sepsis-3 criteria. The primary outcome was hospital mortality. In addition, adjusted logistic regression models was used to evaluate the change in hospital mortality over time. Results: Of 12,645 patients admitted to the ICU during the study period, 5917 patients (46.8 %) met the criteria for sepsis (median age= 65 years [interquartile range: 52, 75], median Acute Physiology And Chronic Health Evaluation Score II [APACHE II] score= 24 [interquartile range: 19, 31], 44.8 % were women and 32.3 % had septic shock). Among patients with sepsis and septic shock, chronic comorbidities were common. Between 2002 and 2017, there was a progressive decrease in APACHE II score and hospital mortality (among patients with sepsis: crude odds ratio (OR) for each 1-year increase 0.95, 95 % confidence interval [CI] 0.94–0.97; APACHE II-adjusted OR 0.96, 95 % CI 0.95–0.98; among patients with septic shock: crude OR 0.93, 95 % CI 0.91–0.95; APACHE II-adjusted OR 0.96, 95 % CI 0.94–0.98). The mortality reduction in patients with sepsis seems to have occurred in the 2010–2017 period (adjusted OR for each 1-year increase 0.88, 95 % CI 0.85–0.91 versus adjusted OR 0.99, 95 % CI 0.96–1.04 for the 2002–2009 period). A similar pattern was observed in patients with septic shock. Conclusions: Patients with sepsis constituted almost half of patients admitted to the ICU. During the 16-year study period, there was a decline in hospital mortality over time among patients admitted with sepsis and septic shock, which occurred mainly from 2010 to 2017.